Developing Seventh-Grade Students’ Vocabulary through Digital Comics: A Case Study Using the Globalcomix Platform - Delvina Siti Nurfatika; Iskhak Said; R. Bunga Febriani (Universitas Galuh, 2026)
Vocabulary development is a crucial component of language learning, particularly for adolescent learners in EFL contexts. In practice, however, many teachers in Majalengka continue to rely on conventional methods that offer limited contextualization for vocabulary instruction. To address this issue, engaging media such as digital comics can be used to motivate students and promote active learning. This study investigates how seventh-grade students acquire new vocabulary through the use of digital comics, focusing specifically on the GlobalComix platform, which remains underexplored in previous research. This study employed a qualitative case study design. Data were collected through non-participant observations that documented the learning activities of 34 seventh-grade students at a public junior high school in Majalengka. An observation checklist served as the primary research instrument, and the data were analyzed using thematic analysis. The findings indicate that GlobalComix supports students’ vocabulary development by providing contextualized input through the combination of text and visual elements. Students demonstrated enthusiasm, active participation, and improved comprehension during the learning process. Overall, GlobalComix offers an enjoyable and effective learning experience that enhances vocabulary understanding and fosters greater engagement in English language lessons. Future research is recommended to explore the long-term impact of digital comics across different educational levels and contexts, as well as to compare their effectiveness with other forms of visual media.